2022
DOI: 10.1039/d2tb00442a
|View full text |Cite
|
Sign up to set email alerts
|

Improving printability of hydrogel-based bio-inks for thermal inkjet bioprinting applicationsviasaponification and heat treatment processes

Abstract: Material jetting bioprinting is a highly promising three-dimensional (3D) bioprinting technique that facilitates drop-on-demand (DOD) deposition of biomaterials and cells at pre-defined positions with high precision and resolution. A major...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 70 publications
0
31
0
Order By: Relevance
“…The control of the physical properties of the polymer was achieved without degrading the functional groups of the polymer, unlike hydrolysis. [ 26 ] This was confirmed by NMR spectroscopy (Figure 3C), and the cell spreading morphology of the 10% 20 h hydrogel also indicated that the cell adhesion motifs (i.e., the RGD motif) were not eliminated after sonication (Figure 6C). As higher concentration inks become printable after sonochemical degradation, hydrogels with improved physical properties could be produced by inkjet printing (Figure 5).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The control of the physical properties of the polymer was achieved without degrading the functional groups of the polymer, unlike hydrolysis. [ 26 ] This was confirmed by NMR spectroscopy (Figure 3C), and the cell spreading morphology of the 10% 20 h hydrogel also indicated that the cell adhesion motifs (i.e., the RGD motif) were not eliminated after sonication (Figure 6C). As higher concentration inks become printable after sonochemical degradation, hydrogels with improved physical properties could be produced by inkjet printing (Figure 5).…”
Section: Discussionmentioning
confidence: 72%
“…[ 25,26 ] However, this chemical treatment inevitably involves the loss of the methacryloyl group, which is the crosslinking site, resulting in a mechanically weaker hydrogel. [ 26 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different systems based on solenoid valves and pressurized material-suppling tubings and on acoustic- and electro-assisted devices have been the alternative to drop-on-demand (DOD) GelMA-based bioprinting; nevertheless, larger drops with the concomitant loss in resolution are unavoidable. A second approach has been to modify further the chemical and structural nature , of GelMA, allowing befitted rheological properties at the expense of losing bioactivity and mechanical resistance post cross-linking.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some challenges faced in translating this to widespread use. Successful production of in-vitro tissue models is dependent on two critical aspects–ability to carry out large-scale manufacturing of cells (growing cells in vast quantities within a homogeneous physical and chemical environment) ( Jordan et al, 2018 ; He et al, 2019 ; Chen et al, 2022 ) and advanced manufacturing platforms (highly-automated fabrication of in-vitro tissue models with high throughput rates and repeatability) ( Ozbolat and Hospodiuk, 2016 ; Ng et al, 2019 ; Zhuang et al, 2019 ; Ng et al, 2020a ; Ng et al, 2020b ; Li et al, 2020 ; Ng et al, 2022 ; Suntornnond et al, 2022 ).…”
mentioning
confidence: 99%